Lembaga Pembentuk Peraturan Perundang-Undangan - Khoirul Amin (Syntax Idea)
Microsoft Office Translator This research was conducted by the author with the aim of knowing more details about state institutions that have the authority to form laws. This study intends to review the 1945 Constitution before it is amended and after the amendment, in addition to reviewing with Law Number: 12 of 2011 concerning the Establishment of Laws and Regulations. The method that the author used in this study, is the normative juridical research method. While the material or data used to answer the problems discussed in this study, by searching and collecting material derived from literature data. The results of this study show that law-forming state institutions are state institutions that take part in the process of forming laws. Before the amendment of the 1945 Constitution, the state institutions authorized to form laws were the People's Consultative Assembly (MPR) and the DPR. And after the amendment of the 1945 Constitution, the authority to form laws changed, consisting of the DPR, the President and the DPD. However, the power to form laws is in the hands of the DPR, while the DPD legislative power is still very limited and only has the authority to participate in discussing draft laws related to Regional Autonomy, Central and Regional Relations, the Establishment of the expansion and processing of natural resources and other economic resources, and the balance of central and regional finances.